Retention strength of carbon fiber reinforced polymer rebar under elevated temperatures - Hyun-Do Yun; Seung-Yun Lee; Dae-Hee Kang; Wonchang Choi (Scientific Reports)
Abstract Understanding the performance of carbon fiber reinforced polymer under elevated temperatures is essential to expanding its application in construction, particularly in fire-prone environments. This study investigates the mechanical behavior of carbon fiber reinforced polymer rebars fabricated through the pultrusion process, which offers superior thermal stability and uniform resin distribution. Tests were conducted to evaluate the tensile strength, elastic modulus, and shear strength of carbon fiber reinforced polymer rebars at temperatures ranging from 25 to 550 °C, exceeding the material’s decomposition temperature. The findings reveal significant degradation in tensile strength and shear strength at elevated temperatures, particularly above 350 °C during the decomposition stage. The tensile strength was more affected by heat than the elastic modulus, with approximately 33% of the initial tensile strength and 20% of the initial shear strength retained at 550 °C. Meanwhile, the elastic modulus decreased to 80%. Despite these reductions, neither tensile nor shear strength converged to zero, indicating some retention capacity under thermal stress. This study also compares its results with empirical equations from the literature and identifies three distinct stages of retention strength associated with elevated temperatures. The insights gained contribute to understanding the thermal degradation mechanisms of carbon fiber reinforced polymer rebars and offer critical data for enhancing the fire resistant design of fiber reinforced polymer reinforced concrete structures.